ANALISIS STRATEGI BISNIS COFFEE SHOP MENGGUNAKAN METODE BUSINESS MODEL CANVAS DAN QUANTITATIVE STRATEGIC PLANNING MATRIX (STUDI KASUS: COFFEE SHOP 'KOPI DUL') - Nadhira Nurul Muhafi (2023)
Coffee Shop Kopi Dul is a Coffee Shop that has been established since 2018. The development of Coffee Shop which is getting higher from year to year requires Coffee Shop Kopi Dul to continue to innovate in order to survive in the midst of existing competition by mapping the business model and creating a business development strategy based on the Company's internal and external factors. The purpose of this research is to plan the business development of Dul Coffee Shop using the Business Model Canvas and QSPM methods. The data processing process in this study begins with tabulating the results of interviews on all Business Model Canvas blocks, conducting the input stage using the IFE and EFE matrices, conducting the matching stage using the IE matrix, SPACE matrix, and SWOT matrix methods, conducting the decision stage using the QSPM method, finally formulating a new Business Model Canvas that has been added to the alternative strategies obtained. The results of the research analysis show that Coffee Shop Kopi Dul is in a hold and maintain position based on the results of the IE matrix, is in the aggressive quadrant based on the results of the SPACE matrix, gets 9 alternative strategy formulations based on the SWOT matrix, and has made a Business Model Canvas that has been improved and added alternative strategy formulations obtained at the matching stage. At the QSPM stage, the alternative strategy that is prioritized is the "Conduct routine competitor observations" strategy with a Sum Total Attractive Score of 6,371.